Multiple sclerosis: patient-reported quality of life in the Świętokrzyskie Region - Brola, Waldemar; Sobolewski, Piotr; Fudala, Małgorzata; Flaga, Stanisław; Jantarski, Konrad (Medical Studies/Studia Medyczne, 2017)
Introduction : Comprehensive epidemiologic data for multiple sclerosis (MS) in Poland are limited. Aim of the research: To analyse patient-reported quality of life and selected clinical and socio-demographic factors of patients registered in the Świętokrzyskie Cohort of the Polish Registry of Multiple Sclerosis (RejSM). Material and methods: Participants were residents of Świętokrzyskie Province, and the data were collected between January 1st 2014 and December 31st 2015 by the RejSM web portal. After registration by doctors, the respondents assessed their quality of life individually using the Polish language versions of self-assessment questionnaires, the EuroQol (EQ-5D and EQ-VAS), and the Multiple Sclerosis Impact Scale (MSIS-29). Results : Of 1525 registered patients, 765 agreed to perform self-assessments of life quality and were included in the study. The mean degree of disability measured with the Expanded Disability Status Scale (EDSS) was 3.8 ±2.3. The mean EQ-5D index score was 0.78 ±0.28, and the mean EQ-VAS score was 65.6 ±23.8. Assessment score with MSIS-29 averaged 86.4 ±22.4 (64.2 ±19.6 for physical state and 24.7 ±7.8 for mental state). Only 34.7% of respondents were economically active. Lower quality of life was significantly associated with higher disability scores (p < 0.001), age over 40 years (p < 0.001), longer disease duration (p < 0.001), no access to therapy (p < 0.001), and unemployment (p = 0.002). No correlation was found between life quality and sex, course of disease, level of education, place of residence, or family status. Conclusions: The main factors decreasing life quality among patients in Świętokrzyskie Province are advanced disability, old age, long disease duration, and limited access to both employment and immunomodulatory treatment.